2016
DOI: 10.1111/acem.13045
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of Shared Decision Making Interventions for Use in Emergency Care: A Research Agenda

Abstract: Decision aids are evidenced-based tools designed to increase patient understanding of medical options and possible outcomes, facilitate conversation between patients and clinicians, and improve patient engagement. Decision aids have been used for shared decision-making (SDM) interventions outside of the ED setting for more than a decade. Their use in the ED has only recently begun to be studied. This article provides background on this topic and the conclusions of the 2016 Academic Emergency Medicine consensus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 51 publications
(58 reference statements)
0
32
0
Order By: Relevance
“…2 Although research in the field of SDM has been ongoing for several decades, recent attention to the opportunities for SDM in the Emergency Department (ED) has heightened the need for ED-specific research. 3,4 Several studies have examined SDM from the perspective of the ED physician, recognizing the importance of the physician-as-stakeholder. 57 These studies have found that physicians often believe their patients do not want to be involved in decisions in the setting of emergency care.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although research in the field of SDM has been ongoing for several decades, recent attention to the opportunities for SDM in the Emergency Department (ED) has heightened the need for ED-specific research. 3,4 Several studies have examined SDM from the perspective of the ED physician, recognizing the importance of the physician-as-stakeholder. 57 These studies have found that physicians often believe their patients do not want to be involved in decisions in the setting of emergency care.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of trying to further validate CT decision tools in low-risk cohorts, we should focus on physician and patient counseling in regard to low disease prevalence and incorporate this guidance within a shared decisionmaking intervention. 3 When compared with "usual care" in a randomized controlled trial, such an intervention may be significantly more effective in reducing CT imaging in low-risk populations.…”
Section: Abandoning Further Study Of the Application Of Computed Tomomentioning
confidence: 99%
“…20 In 2016, the Academic Emergency Medicine (AEM) Consensus Conference on SDM in the ED called for further research on the development and testing of SDM interventions and identified syncope as a relevant clinical scenario. 21 Priority research questions identified during this conference included how to communicate risk and uncertainty with patients, what tools can facilitate SDM, and what outcomes are suitable for SDM research in the ED.…”
mentioning
confidence: 99%